Pick n Pay : changing its environmental footprint - Alsfine, Karen; Luiz, John ([London] : SAGE, 2016)
Pick n Pay has identified climate change, and the carbon emissions that are contributing to the global phenomenon, as presenting a risk not only to the business, but to broader sustainability as well. This book examines Pick n Pay's plan to reduce its overall carbon footprint - and specifically its energy consumption - by 20% per square metre of trading space by 2012.
Originally Published in: Alsfine, K., & Luiz, J. (2008). Pick n Pay: Changing its Environmental Footprint. WBS-2008-10. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Pick n Pay (Firm); Environmental responsibility -- Economic aspects -- Case studies; Industries -- Environmental aspects -- Case Studies